MicroRNAs: As A Novel Potential Tool for Diagnosis, Prognosis, and Therapeutic Agents in Hypertension. - Jalnapurkar Sawan; Mangaonkar Abhishek; Mondal Ashis; Burke John; Fulzele Sadanand; Kolhe Ravindra (Journal of Hypertension and Cardiology, 2015)
The aim of this review is to compile our understanding of microRNA (miRNA) and its significance in Hypertension (HTN) pathophysiology. The wide spectrum of health disparity is one of the reasons for the dominance of HTN in humans for decades. We are striving hard to understand these variations, and we know to some extent that genetic susceptibilities do exist in HTN. Understanding miRNA will add to the current understanding of the disease process. In later parts, we discussed possible clinical implications of miRNAs in HTN as a biomarker of disease expression and its potential in prognostic and therapeutic applications in HTN.
Keywords: microRNA/miRNA